Advantage of a disposable focusing lens in petawatt laser for inertial confinement fusion. (September 2021) - Li, Jiamei; Li, Dawei; Yu, Hui; Lv, Fengnian; Zhou, Qiong; Lu, Xingqiang
Highlights: The refractive focusing on ps-petawatt laser is possible in ICF. A disposable lens replaces the parabolic mirror with debris shield. It can save the target chamber space and achieve higher focal power. B-integral can be partly corrected by deformable mirror with ν cutoff  = 0.0625 mm −1 and a better focal spot can be achieved. Abstract: The inertial confinement fusion laser facility usually has several hundred large-aperture laser beams. A focusing off-axis parabolic (OAP) mirror combined with a debris shield to focus the petawatt lasers must be placed outside the target chamber for target space limitation. Further increasing the focusing power density of ps-petawatt lasers for large F-number focusing is difficult. However, a disposable lens with a smaller F-number that is used to simultaneously replace the parabolic mirror and debris shield can be placed inside the chamber by an extension pipe. The lens only needs a small target space and can increase the focusing power density of the petawatt laser over 35 times more than an OAP mirror under a 20° solid angle. The nonlinear effect of self-phase modulation may decrease the quality of the spot distribution, but under the correction of a deformable mirror with ν cutoff  = 0.0625 mm −1, a better focusing spot distribution can be obtained.